Understanding Ride-Hailing Adoption Among Generation Z in Malang: An Integrated TPB-TAM Framework - Putri, Amalia Romadhona Ghiffarri; Darmawan, Vertic Eridani Budi; Chen, Yuh Wen (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study examines the factors influencing the choice of ride-hailing modes among Generation Z (15-29 years old) in Malang City, given their dominance as the largest user group of ride-hailing services in Indonesia. The analysis will combine the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) to understand the key drivers behind their decisions to use ride-hailing services. The study surveyed 406 respondents through purposive sampling, focusing on residents of Malang who actively use ride-hailing services such as Grab, Gojek, Maxim, or inDrive. SEM was used to explain the relationships among variables, whereas MGA-PLS was applied to analyze differences by gender and vehicle ownership. Results also show that Ease of Use (KPN) significantly influences Usefulness (K) of the ride-hailing service. While both variables also positively influence Attitudes toward ride-hailing, leading to a stronger Intention to choose these services. Furthermore, Attitude (S) and Subjective Norm (NS) appear to be significant predictors of Intention (N), which in turn has a substantial impact on Behavior. The MGA-PLS results indicate that females are more influenced by Ease of Use (KPN) and Usefulness (K), whereas car owners tend to rely more on Ease of Use (KPN) when assessing Usefulness (K). These findings not only strengthen the integrated TPB-TAM framework in the context of secondary cities in Indonesia but also offer practical insights for designing more targeted and inclusive ride-hailing strategies based on user demographics.